Mid-ventricular hypertrophic cardiomyopathy with apical aneurysm: a multimodality imaging case report - Martinez-Dominguez, Pavel (2025)
Mid-ventricular hypertrophic cardiomyopathy is a rare subgroup within hypertrophic cardiomyopathies that may present with apical aneurysm. This condition is associated with an increased risk of cardiac adverse events, including cardiac arrest, heart failure, thromboembolic events, or sudden cardiac death. We present a case of a 41-year-old man who presented with a history of exertional dyspnea and syncope. Multimodality imaging with echocardiography and cardiac magnetic resonance showed hypertrophy of the mid-ventricular segments with apical aneurysm. An implantable cardioverter-defibrillator was implanted to prevent sudden cardiac death.